Late-Onset Endophthalmitis Secondary to Exposed Glaucoma Tube Implant in a Rare Case of Paediatric Glaucoma. (17th December 2011) - Ranganath, Akshatha; Hashim, Adnan
Abstract : Glaucoma drainage implants (GDIs) are used to treat paediatric glaucoma resistant to conventional medical and surgical treatment, achieving good intraocular pressure (IOP) control and long-term success. Late endophthalmitis is a rare complication that may develop following GDI surgery. A 17-year-old male presented with acute endophthalmitis 2 years after Ahmed glaucoma valve implantation with pericardial patch graft for management of refractory glaucoma secondary to congenital ectropion uveae. The glaucoma tube was exposed due to erosion of the overlying conjunctiva with no visible pericardial graft. After control of active infection, he underwent tube revision surgery whereby the exposed tube was retained and repatched with a double-thickness pericardial patch graft. He did well following surgery with good control of IOP and restoration of vision. Conjunctival dehiscence with graft melting over the GDI tube presented a major risk factor for endophthalmitis. Prompt surgical revision of an exposed tube is highly recommended to avoid ocular morbidity.